GWAS analysis of Fusarium head blight resistance in a Nordic-Baltic spring wheat panel - Syed, Shayan; Aleliūnas, Andrius; Armonienė, Rita; Brazauskas, Gintaras; Gorash, Andrii (Frontiers in Plant Science, 2025)
Genetic improvement of wheat resistance to the devastating disease Fusarium head blight (FHB) is the most effective strategy to prevent economic, health, and food safety issues, and is also an environmentally friendly approach for disease control. However, wheat breeding for FHB resistance is hampered by complex resistance, which is controlled by multiple loci with minor effects and limited availability of resistance sources. Globally, sources of FHB resistance primarily stem from Asian wheat; however, excellent resistance has also been noted in European spring wheat cultivars and breeding lines. The success of breeding for the improvement of wheat resistance to FHB relies on the availability of a genetic pool that is adapted to local environments, possesses desirable agronomic traits, and includes a sufficient number of effective QTL for wheat resistance to FHB. A genome-wide association study (GWAS) was performed using a panel of 332 spring wheat genotypes including 181 from Baltic, Nordic countries (65), Central and Western Europe (76) and exotic genotypes (10), employing a 25 K single nucleotide polymorphism (SNP) array. The objectives of this study were to identify SNPs significantly associated with wheat resistance, determine QTL with approximate regions, and identify candidate genes within these QTL by exploring a panel of wheat genotypes adapted to the Baltic and Nordic countries. A total of 65 significant marker-trait associations (MTAs) with FHB resistance were identified using GWAS. Resistance loci were distributed across 15 wheat chromosomes and three genomes. Furthermore, 55 QTL were identified, 10 of which had phenotypic variation explained (R2) values above 10%. QFHB-2AL.1 and QFHB-2BL.1 were stably detected in 11 trials. An overall total of 52 candidate genes was identified by analyzing QTL regions in combination with published transcriptome data. This study demonstrated that a substantial number of QTL can be found in European spring wheat germplasm. Pyramiding of major effects along with small-effect QTL resulted in a positive additive effect on wheat resistance. Elite breeding lines with multiple resistance alleles were identified and could be used as valuable sources in wheat breeding for FHB resistance.